Adult's Dietary Intakes of Selected Vitamins & Minerals Essential for Energy Metabolism and Cognition: A Comparison Across Countries & Genders (FS10-04-19) - Tardy, Anne-Laure (Curr Dev Nutr, 2019)
OBJECTIVES: Vitamins and minerals dietary intake recommendations rely on their role on energy-yielding metabolism, cognitive functions and fatigue relief. However, even in adult populations, reliable information on the actual dietary intake is not easily available. In this study, possible gaps between recommendation and actual intake of these micronutrients were assessed in adult European (Spain &Turkey), American (USA, Brazil & Mexico) and Asian (Vietnam) populations. It aimed to provide an overview of the risk of inadequate intake and to identify potential variations across geographic regions and genders. METHODS: In each country, information was retrieved from representative nation-wide dietary survey, government reports and Medline scientific publications. Prevalence of inadequate intake was classified as the proportion of the population group with an intake below the estimated average requirement (EAR) as follows: <15%: low risk (green); 15 to 40%: possible risk (yellow); 41 to 75%: real risk (orange); >75%: high risk (red). RESULTS: The risk of inadequate intake of micronutrients known for their role on physical and mental performance varied across nutrients, genders and countries (Table 1). Some common features were identified across the six countries such as a higher risk of deficiency in women compared to men and in developing vs developed countries. Certain specific risks were identified namely a high risk of inadequate folate intake in Spain, a wide geographical risk of inadequate vitamin C intake even where fruits should be easily available, and a general risk for most micronutrients in Turkey. CONCLUSIONS: Inadequate dietary intakes are far from being uncommon in most countries in the selected micronutrients that are key for the energy metabolism, cognitive functions and fatigue relief. Therefore, diets and nutritional education need constant improvement worldwide, and dietary supplements could be helpful by closing the gaps between the recommended and the actual intakes. FUNDING SOURCES: This study has been sponsored by Sanofi. SUPPORTING TABLES, IMAGES AND/OR GRAPHS: